(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This article clarifies the concept of intercultural communication and education and related terminology. Intercultural education is as important in today’s world as the ability to read, write, count and use computers. This requires new directions for different points of view and life experiences. The article provides methodological recommendations for teaching and educating intercultural communicative competence through empathy, and not in the form of education, language learning, competition and conflict.